2021
DOI: 10.3389/fcell.2021.783322
|View full text |Cite
|
Sign up to set email alerts
|

m6A Methylation Regulates Osteoblastic Differentiation and Bone Remodeling

Abstract: Osteoporosis is a prevalent bone disease of the aging population, which is characterized by a decrease in bone mass because of the imbalance of bone metabolism. Although the prevention and treatment of osteoporosis have been explored by different researchers, the mechanisms underlying osteoporosis are not clear exactly. N6 methyladenosine (m6A) is a methylated adenosine nucleotide, which functions through its interaction with the proteins called “writers,” “readers” and “erasers.” The epigenetic regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 88 publications
1
45
0
Order By: Relevance
“…m6A methylation has been documented to be the most pervasive internal mRNA modification in eukaryotes, which plays important roles in affecting RNA metabolism including RNA splicing, translation, stability, and translocation ( 41 ). Numerous studies demonstrated that regulators of m6A RNA methylation were involved in bone homeostasis and human osteogenesis diseases ( 42 44 ). More importantly, dysregulation of m6A has also been associated with the initiation and progression of spinal ligament ossification disorders.…”
Section: Discussionmentioning
confidence: 99%
“…m6A methylation has been documented to be the most pervasive internal mRNA modification in eukaryotes, which plays important roles in affecting RNA metabolism including RNA splicing, translation, stability, and translocation ( 41 ). Numerous studies demonstrated that regulators of m6A RNA methylation were involved in bone homeostasis and human osteogenesis diseases ( 42 44 ). More importantly, dysregulation of m6A has also been associated with the initiation and progression of spinal ligament ossification disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathways also played important roles in the regulation of bone homeostasis, which was supposed to be regulated by N6 methyladenosine (m6A). At the cellular level, m6A modi cation has been known to affect cell proliferation, differentiation, and apoptosis of bonerelated cells, such as bone marrow mesenchymal stem cells (BMSC), osteoblasts, and osteoclasts by regulating the expression of ALP, Runx2, Osterix, VEGF, and other related genes [31] . Thus, m6A modi cation may also provide a new approach for AS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…At the RNA level, more than 100 post-transcriptional modifications have been identified, while m6A methylation is one of the most common modifications in mammals that regulate post-transcriptional gene expression without changing the base sequence [ 126 ]. m6A methylation is mainly involved in many biological processes and diseases through three types of proteins: methyltransferases, methylation readers and demethylases [ 127 ]. Among them, m6A demethylases, such as Alpha-ketoglutarate-dependent dioxygenase FTO (FTO), can remove m6A methylated groups in RNA, which is the basis for the dynamic reversibility of methylation [ 127 ].…”
Section: Mirnas Mediating the Regulation Of Bmsc-evs On Bone Metabolismmentioning
confidence: 99%
“…m6A methylation is mainly involved in many biological processes and diseases through three types of proteins: methyltransferases, methylation readers and demethylases [ 127 ]. Among them, m6A demethylases, such as Alpha-ketoglutarate-dependent dioxygenase FTO (FTO), can remove m6A methylated groups in RNA, which is the basis for the dynamic reversibility of methylation [ 127 ]. FTO, also known as fat mass and obesity-associated protein, is one of the key elements in regulating body weight and fat mass, mainly by affecting lipogenesis [ 128 ].…”
Section: Mirnas Mediating the Regulation Of Bmsc-evs On Bone Metabolismmentioning
confidence: 99%